PREVALENSI BAKTERI Salmonella PADA AYAM POTONG YANG DIJUAL DI PASAR TRADISIONAL PANGKALPINANG - Eva Safitri; Nur Annis Hidayati; Rossy Hertati (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2019)
Salmonella bacteria is a pathogenic bacterium that can multiply in the digestive tract of animals and humans. The presence of Salmonella in the digestive system causes Salmonella contamination is often associated with the mouth through food contaminated with Salmonella. The Center for Science in The Public Interest (CSPI) states that chicken meat ranks first in food contaminated with pathogenic bacteria such as Salmonella. This study aims to calculate the prevalence of Salmonella bacteria in chicken carcass in traditional markets, Pangkalpinang. The method used is descriptive with quantitative survey methods. The results showed that the prevalence of Salmonella bacteria in Pagi market, Putih market, and Ratu Tunggal market were 41.2%, 50% and 0%.